The Role of Non-Governmental Organizations Dealing with Disastrous Floods in Pakistan in the Year 2022 - Omer, Sonia; Jabeen, Sadia; Granich, Steven (Annals of Human and Social Sciences, 2024)
The objective of this study is to explore role of non-governmental organizations to mitigate their effects of floods on Pakistan's economy and the measures taken by these organizations.Pakistan has been facing severe floods over the past few years, causing significant damage to its economy. The floods have had a massive impact on agriculture, infrastructure, and human lives, resulting in long-term economic consequences.In this context, the role of national and international donor agencies is very important. So in this context this study is an attempt to find out the role of these non-governmental organizations in the flood of year 2022.Three non-governmental organizations i.e.Bunyad Foundation, Akhuwat, and Agahi Pakistan, which were active participants in rehabilitation services in the flood-ridden areas of the country during the flood of 2022. The purposive sampling technique was followed, and researchers conducted nine interviews with staff of non-governmental organizations that assisted victims of the floods. Thematic analysis was used for the sake of analysis. The findings throw light on the challenges in initial relief work, the outpouring of aid and difficulties in managing aid related matters and the focus on the sustainable development. The research highlights the challenges in helping victims, the aid effort, and sustainable development in these flood-prone areas of Pakistan.The study further concludes that these organization, specifically in the times of crisis in Pakistan have shown great resilience and have provided people support and aid. There has been gap of collaborations between state institutions and these non-governmental organizations. With improved cooperation of non-governmental organizations and the state, the people of Pakistan can benefit. So there is need to develop a liaison between the two.